World Economy Autumn 2021 - Stumbling blocks on the road to recovery - Klaus-Jürgen Gern; Philipp Hauber; Stefan Kooths; Ulrich Stolzenburg (Kiel Institute for the World Economy (IfW), 2021)
The German economy is picking up speed again. After the resurgence of the Covid-19 pandemic had interrupted the economic recovery in the winter half-year, GDP will expand at a fast pace in the further course of the year and exceed its pre-crisis level again. With the removal of the pandemic-related restrictions, activity will rebound, especially in those areas that were previously particularly burdened. Retail trade and contact-intensive services in particular are likely to benefit from the rebound in private household consumption. For the time being, however, the recovery will be delayed in the manufacturing industry. The strong global recovery has brought with it multi-layered supply bottlenecks that are noticeably hampering production in many firms. Despite the very good order situation, production in the manufacturing industry will therefore probably only gradually return to its recovery path in the second half of the year, provided that the supply bottlenecks then gradually ease. With the supply bottlenecks, price pressures have also increased, especially as economic momentum is high worldwide. Thus, prices for raw materials, intermediate goods and transport services have recently been on a broad upward trend. All in all, GDP is expected to grow by 3.9 percent this year and by 4.8 percent in 2022. Consumer prices will rise at a much faster rate of probably 2.6 percent this year and by around 2 percent in 2022.
Keywords: 330; advanced economies; emerging economies; monetary policy; COVID19